A mulher no fim do mundo : identidade da mulher negra no discurso das biografias jornalísticas de Elza Soares - Silva, Jéssica Tamires Feijó da (2024)
Biographies have a close relationship with history and literature, but they also represent a cultural corpus and an editorial market that has been strengthened by the inclusion of journalism in these productions, generating reflections from this third field as well. In this context, this dissertation analyzes the discursive practice in the journalistic biographies of Brazilian singer Elza Soares, based on the following guiding question: How do the two biographies of Elza Soares (Louzeiro, 1997; Camargo, 2018) reflect the discursive elaboration of race and gender identity? As an investigative method, three levels of observation are proposed, ranging from the search for an understanding of historical and cultural contexts of the object to the interpretation of statements that allow for the investigation of the black woman’s identity as a discursive regularity (Foucault, 2008). To navigate this, we resort to multidisciplinary reflections on narrative (Martinez, 2016; Motta, 2022; Silva, 2005), identity (Bauman, 2005; Hall, 2006; Woodward, 1997) and intersectionality (Hirata, 2014; Akotirene, 2018; Crenshaw, 2002), in addition to the innovative perspectives of Almeida (2020), Hooks (2019a; 2019b; 2020) and Kilomba (2019). At the end of the investigation, it is observed that the biographical narratives showed deviations in discourse instruments such as the choice of approaches in thematic trajectories, the use of sources, and the interference of the biographer/author, in addition to the categories of transparency and extraordinariness (Vilas-Boas, 2008). On the other hand, when approaching the story of Elza Soares, the narratives also demonstrated socially constructed regularities about the identity of the black woman, implicated by a structure of colonialist patriarchy that tries to keep black women in roles linked to the idea of otherness: the other sexual object, the other exotic, the other subservient, the other to care for. In this sense, Elza’s uniqueness is exalted by transgressing this historically constructed imaginary, but always at the cost of oppression such as internalized guilt that demands compensation/remission from those who infringe it. Despite the objectification/dehumanization that black women must confront, they develop their own discourse in order to occupy the position of a subject - the one who develops their own identity.